In vitro intestinal permeability studies, pharmacokinetics and tissue distribution of 6-methylcoumarin after oral and intraperitoneal administration in Wistar rats - Paola Andrea Cárdenas; Jadel Müller Kratz; Aura Hernández; Geison Modesti Costa; Luis Fernando Ospina; Yolima Baena; Cláudia Maria Oliveira Simões; Álvaro Jimenez-Kairuz; Marcela Aragon (Universidade de São Paulo, 2017)
ABSTRACT 6-Methylcoumarin (6MC) is a semisynthetic coumarin with important in vitro and in vivo anti-inflammatory activity. In order to continue the pre-clinical characterization of this molecule, in vitro intestinal permeability, plasma profile and tissue distribution after oral administration in rats were studied. The permeability of 6MC was evaluated by the Caco-2 cellular model in both the apical-basal (A-B) and basal-apical (B-A) directions. The pharmacokinetics and biodistribution were evaluated in rats after oral and intraperitoneal administration at doses of 200 mg/kg. Transport experiments with Caco-2 cells showed that 6MC presented high permeability at all concentrations evaluated. This finding suggested that 6MC could be transported across the gut wall by passive diffusion. The plasma concentration-time curve showed that the maximum concentration (Cmax) was 17.13 ± 2.90 µg/mL at maximum time (Tmax) of 30 min for the oral route and Cmax 26.18 ± 2.47 µg/mL at 6.0 min for the intraperitoneal administration, with elimination constant of (Ke ) 0.0070 min-1 and a short life half time of (T1/2 ) lower that 120 min. The distribution study showed that 6MC has high accumulation in the liver, and widespread distribution in all the organs evaluated.